GDF11 Implications in Cancer Biology and Metabolism. Facts and Controversies - Simoni-Nieves, Arturo; Gerardo-Ramírez, Monserrat; Pedraza-Vázquez, Gibrán; Chávez-Rodríguez, Lisette; Bucio, Leticia; Souza, Verónica; Miranda-Labra, Roxana U.; Gomez-Quiroz, Luis E.; Gutiérrez-Ruiz, María Concepción (Frontiers in Oncology, 2019)
Growth Differentiation Factor 11 (GDF11), a member of the super family of the Transforming Growth Factor β, has gained more attention in the last few years due to numerous reports regarding its functions in other systems, which are different to those related to differentiation and embryonic development, such as age-related muscle dysfunction, skin biology, metabolism, and cancer. GDF11 is expressed in many tissues, including skeletal muscle, pancreas, kidney, nervous system, and retina, among others. GDF11 circulating levels and protein content in tissues are quite variable and are affected by pathological conditions or age. Although, GDF11 biology had a lot of controversies, must of them are only misunderstandings regarding the variability of its responses, which are independent of the tissue, grade of cellular differentiation or pathologies. A blunt fact regarding GDF11 biology is that its target cells have stemness feature, a property that could be found in certain adult cells in health and in disease, such as cancer cells. This review is focused to present and analyze the recent findings in the emerging research field of GDF11 function in cancer and metabolism, and discusses the controversies surrounding the biology of this atypical growth factor.